The 150 faces of the Observatory: innovative projects for school education and science communication - Corbelli, Edvige; Zanazzi, Alessandra (Il Colle di Galileo, 2023)
Over the years, the staff of the INAF-Osservatorio di Arcetri has always planned new opportunities and events for public outreach and education. Countless meetings and events with the public and with students are not only tools for disseminating astronomy, but also moments of collective growth, thanks to the sharing of that enchantment and wonder that each of us feels when we look at the sky.